Peran Intervensi Berbasis Humor dalam Menurunkan Tekanan Darah: Bukti dari Studi Kasus di Pelayanan Kesehatan Primer - Simunati Simunati; Ratna Mahmud; Ismail Ismail; Ade Nurkhotimah; Sry Wahyuni Mansur (Celebes Health Journal, 2025)
Background: Hypertension is a major public health problem worldwide and a leading risk factor for cardiovascular morbidity and mortality. In Indonesia, the prevalence of hypertension continues to rise, with South Sulawesi ranked among the highest cases. Non-pharmacological approaches are increasingly promoted as complementary strategies to enhance blood pressure control. One promising method is laughter therapy, which has been reported to improve mood, stimulate endorphin release, and reduce vascular tension. Objective: This study aimed to evaluate the effectiveness of laughter therapy in reducing blood pressure among patients with hypertension. Methods: This research employed a descriptive case study design conducted in April 2024 at the working area of Gentungang Public Health Center, Gowa District. One hypertensive patient, aged 43 years, was purposively selected as the study subject. Laughter therapy in the form of humor-based video sessions was administered three times over one week. Blood pressure was measured before and after each intervention, accompanied by observation and patient self-report regarding physical and emotional responses. Results: The results showed a consistent reduction in blood pressure across all sessions. Average systolic pressure decreased by 16.3 mmHg and diastolic pressure by 7.6 mmHg. The patient also reported diminished headaches, improved sleep quality, and enhanced mood after the intervention. No adverse effects were observed during the therapy. Conclusions: In conclusion, laughter therapy demonstrated effectiveness as a complementary non-pharmacological intervention for lowering blood pressure in hypertensive patients. These findings suggest its potential integration into nursing practice, particularly in primary health care settings, to support holistic hypertension management.